2012
DOI: 10.1038/oby.2011.301
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity Paradox in Amputation Risk Among Nonelderly Diabetic Men

Abstract: The association between BMI and amputation risk is not currently well known. We used data for a cohort of diabetic patients treated in the US Department of Veterans Affairs Healthcare System in 2003. Men aged <65 years at the end of follow-up were examined for their amputation risk and amputation-free survival during the next 5 years (2004–2008). Compared to overweight individuals (BMI 25–29.9 kg/m2), the risks of amputation and treatment failure (amputation or death) were higher for patients with BMI <25 kg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…BMI was associated with Charcot foot but not with DFU or amputation. Our findings are consistent with those previously reported for obesity with Charcot foot and amputation (14; 25). Our findings differ from Sohn and colleagues for obesity and foot ulcer risk.…”
Section: Discussionsupporting
confidence: 94%
“…BMI was associated with Charcot foot but not with DFU or amputation. Our findings are consistent with those previously reported for obesity with Charcot foot and amputation (14; 25). Our findings differ from Sohn and colleagues for obesity and foot ulcer risk.…”
Section: Discussionsupporting
confidence: 94%
“…Given the likely role of body weight in leading to greater plantar pressure, a cause of diabetic foot ulcer, one would have expected greater weight to be associated with greater amputation risk (24). Another possibility to explain this association is a variant of the "obesity paradox" that has been demonstrated in multiple diseases, including diabetes, with lower incidence of multiple health outcomes associated with greater body weight, including mortality and amputation, possibly due to reverse causation (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Gaesser cites a list of conditions that are less common in people in the 'obese' BMI category than in the 'healthy weight' BMI category: lung, stomach, colon and esophageal cancer, malignant melanoma, premenopausal breast cancer, chronic bronchitis, tuberculosis, mitral valve prolapse, anemia, type 1 diabetes, premature menopause, and osteoporosis (Gaesser, 2002(Gaesser, , 2010. There are a range of cardiovascular conditions in which people in the 'obese' BMI category have a more favorable survival risk than people in the 'healthy' weight BMI category including aortic atherosclerosis (Barth, Maximilian Buja, Cao, & Brodsky, 2017;Brodsky et al, 2016), hypertension, heart failure (Komukai, 2012;Zapatero et al, 2011), percutaneous revascularization, coronary artery bypass graft surgery, treadmill referrals, peripheral arterial disease, echocardiography referrals, and co-morbid CVD and T2DM (Davenport et al, 2009;Doehner et al, 2012;Hong et al, 2012;Lavie, Milani, & Ventura, 2009;Raiszadeh & Travin, 2010;Sohn et al, 2011;Uretsky et al, 2010). A pooled analysis of five longitudinal studies looking at mortality risk of people with incident T2DM showed that for people in the 'healthy' weight BMI category compared with people in the 'overweight' and 'obese' BMI categories, after controlling for demographic characteristics, blood pressure, lipid levels, waist circumference, and smoking status, the hazard ratio for total mortality was 2.08, for CVD mortality was 1.52, and for non-CVD mortality was 2.32 (Carnethon et al, 2012).…”
Section: Contributing Factor Citationmentioning
confidence: 99%